KUALITAS PELAYANAN PUBLIK UNTUK MENINGKATKAN KEPUASAN MASYARAKAT DI KANTOR KELURAHAN BULAK BANTENG KOTA SURABAYA - Miftahul Miftahul; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2022)
The Village Office is one of the agencies that has an important role in providing quality services to every community. But the fact is that until now there are still many people who complain about the services provided by employees at the Bulak Banteng Village Office, Surabaya City. The problems that exist are poor service, length of services process until there is no solutions related to problems experienced by the community during the services process. This study aims to describe the quality of public sevices to increase community satisfaction in the Bulak Banteng Village Office, Surabaya City by using the six indicators proposed by Mahmudi which include, transparency, accountability, conditional, participatory, non-disriminatory, balance of rights and obligations. The study uses adescriptive research method with a qualitative approach. Data collection techniques in this study used interview techniques, observation, literature studies from books, journals and documentation studies, whilw to analyze data using the Miles And Huberman model. The results showed that the quality of service provided by employees at the Bulak Banteng Village Office in Surabaya was good, starting from the openness of employees in explaining information, employee responsibilities in completing tasks to the responsiveness of employees to solve community problems during the service process. Keywords: Public service, Public quality, Society statisfaction